JOURNAL OF GOVERNMENT & POLITICS : Democratic Model of Public Policy Accountability. Case Study on Implemntation of Street Vendors Empowerment Policy in Makassar City - Rulinawaty Kasmad , Alwi (FISIPOL UMY, 2015)
Policy accountability is a form of manifestation of public officials responsible to the people.